G-CSF does not influence C2C12 myogenesis despite receptor expression in healthy and dystrophic skeletal muscle - Wright, Craig R.; Brown, Erin L.; Della-Gatta, Paul A.; Ward, Alister C.; Lynch, Gordon S.; Russell, Aaron P. (Frontiers in Physiology, 2014)
Granulocyte-colony stimulating factor (G-CSF) increases recovery of rodent skeletal muscles after injury, and increases muscle function in rodent models of neuromuscular disease. However, the mechanisms by which G-CSF mediates these effects are poorly understood. G-CSF acts by binding to the membrane spanning G-CSFR and activating multiple intracellular signalling pathways. Expression of the G-CSFR within the haematopoietic system is well known, but more recently it has been demonstrated to be expressed in other tissues. However, comprehensive characterization of G-CSFR expression in healthy and diseased skeletal muscle, imperative before implementing G-CSF as a therapeutic agent for skeletal muscle conditions, has been lacking. Here we show that the G-CSFR is expressed in proliferating C2C12 myoblasts, differentiated C2C12 myotubes, human primary skeletal muscle cell cultures and in mouse and human skeletal muscle. In mdx mice, a model of human Duchenne muscular dystrophy (DMD), G-CSF mRNA and protein was down-regulated in limb and diaphragm muscle, but circulating G-CSF ligand levels were elevated. G-CSFR mRNA in the muscles of mdx mice was up-regulated however steady-state levels of the protein were down-regulated. We show that G-CSF does not influence C2C12 myoblast proliferation, differentiation or phosphorylation of Akt, STAT3 and Erk1/2. Media change alone was sufficient to elicit increases in Akt, STAT3 and Erk1/2 phosphorylation in C2C12 muscle cells and suggest previous observations showing a G-CSF increase in phosphoprotein signalling be viewed with caution. These results suggest that the actions of G-CSF may require the interaction with other cytokines and growth factors in vivo, however these data provides preliminary evidence supporting the investigation of G-CSF for the management of muscular dystrophy.